The Roles Of Islamic Social Welfare Assistant (Zakat) For The Economic Development Of New Convert - Johari F., Aziz M.R.A. (2018)
This study demonstrates literately the importance of social welfare assistant (Zakat) towards the economic development among new convert. As one of the several instruments by Islam, Zakat is important to combat and enhance welfare in the society. It also helps to generate a flow of funds and recruit the necessary manpower. Meanwhile, new convert Muslims has just made the biggest decision of their lives and changed their religion as well as their way of live to one that they are unfamiliar with in many ways. Thus, Zakat plays significant role in enhancing economic development in order 'to win' and 'to soften' the heart of the new convert to follow Islam as a way of life. Previous Islamic scholar agreed that the term new convert also includes non-Muslims, but only for the purpose of turning their hearts to Islam. The objective of this article is to explore the problems of new converts and the contribution of Zakat towards reducing their problems. Qualitative method based on document analysis and interview with recent officer are used in this article. This article is trying to answer the type of problem that new convert are facing and trying to look at Zakat distribution as the solution for their problems. © IDOSI Publications, 2013.